PROBLEMATIKA DIMENSI DAN STRATEGI PENINGKATAN KUALITAS PENDIDIKAN DI INDONESIA - Hasby Assidiqi, Muhammad; Dzul Azmi, Muhammad; Apriliantoni (LPPM STAI Muhammadiyah Probolinggo, 2025)
Education is a crucial element in a nation's development, influencing not only individuals but also broader social and economic progress. In Indonesia, improving the quality of education is a top government priority, with a focus on sustainable enhancement through integrated strategies and dimensions. This study identifies educational dimensions encompassing personal, social, and cultural aspects, aligning with the goals outlined in Law No. 20 of 2003. Strategies for improving educational quality, such as school-based management, fostering positive school culture, and effective leadership, are outlined as key steps toward achieving desired outcomes. The quality of education in Indonesia faces significant challenges, including a lack of qualified teachers, inadequate infrastructure, and curriculum policies. Government initiatives to address these issues include innovative policies like the Merdeka Belajar program and improvements in digital infrastructure. This research employs a qualitative methodology using a literature study approach to analyze educational challenges and propose applicable solutions. Findings indicate that collaboration among the government, society, and educational institutions is essential for creating a high-quality, internationally competitive learning environment. With commitment from all stakeholders, it is expected that the quality of education in Indonesia will improve significantly in the near future. The influence of entertainment platforms such as social media, television, and others significantly impacts individuals across Indonesia. It would be prudent for the government, schools, and parents to develop strategies and take action to increase the presence of inspirational educational content while limiting immoral and non-educational material. This effort aims to foster an educated and highly knowledgeable Indonesian society that embodies a harmonious and civilized way of life.